ENT600: Smart fogger / Mohd Subky Ismail, Edzatul Noradiah Durimi and Jessica Joseph - Ismail, Mohd Subky; Durimi, Edzatul Noradiah; Joseph, Jessica (2018)
Dengue fever (DF) causes a lot of suffering to mankind. DF is a mosquito-borne disease that caused by any one of four dengue fever virus serotypes which are DENV-1, DENV-2, DENV-3 and DENV-4 and belonging to the genus Flavivirus, family Flaviviridae. They are spherical in shape, lipid-enveloped, 40-50-mm single-stranded RNA particles which share structural and pathogenic features but have distinct genetic and serological characteristics. The relationships between the serotypes and transmission efficiency or disease expression are uncertain, but DENV-2 and DENV- 3 are likely to contribute the most to disease severity and death. Dengue is endemic to tropical and subtropical countries and is the arboviral disease that has spread most rapidly among the tropical and subtropical regions of the planet. It also can behave in an epidemic fashion when appropriate conditions exist. The occurrence of conditions that favor endemicity and epidemic, namely the presence of large territories with Aedes mosquito breed, sizeable susceptible human groups and the continuous introduction and/or circulation of one or more serotypes are factors responsible for endemic and epidemic. Environmental parameters such as temperature and precipitation affect the demography and behavior of Aedes, therefore climate, the disordered increase in the global population, international travel, poverty and lack of sustained program at various levels are assumed contributing factors. However, the specific contribution of each factor is difficult to measure. Preventing or reducing dengue virus transmission depends entirely in controlling the mosquito vectors or interruption of human-vector contact. WHO promotes the strategic approach known as Integrated Vector Management (IVM) to control mosquito vectors, including those of dengue. One of IVM to control mosquito vectors with thermal fogging machine, however some studies show that the machine can cause ergonomic problem to the handler.